Experiencing live composite video lectures : comparisons with traditional lectures and common video lecture methods - Rosenthal, Sonny (2020)
Video compositing can be used to combine images of the instructor and content, which the instructor can monitor in real time. We evaluated the student experience of this “live composite” format in two carefully designed experiments. Results showed the perceived quality of and student preference for live composite lectures is not different from that of traditional lectures. Results also showed the live composite format is superior to voiceover and picture-in-picture formats in terms of attention, positive emotion, experiential attitude, preference, perceived quality, and instructor social presence. The two experiments had similar patterns of results, suggesting the observed effects are robust. Although we found no differences in short-term learning among lecture formats, the live composite method resulted in a better subjective experience for students. Instructors who use online recordings should consider adopting this approach.